Modulation of the Wheat Seed-Borne Bacterial Community by Herbaspirillum seropedicae RAM10 and Its Potential Effects for Tryptophan Metabolism in the Root Endosphere - Carril, Pablo; Cruz, Joana; di Serio, Claudia; Pieraccini, Giuseppe; Ait Bessai, Sylia; Tenreiro, Rogério; Cruz, Cristina (Frontiers in Microbiology, 2021)
Plants and their associated microbiota share ecological and evolutionary traits that are considered to be inseparably woven. Their coexistence foresees the use of similar metabolic pathways, leading to the generation of molecules that can cross-regulate each other´s metabolism and ultimately influence plant phenotype. However, the extent to which the microbiota contributes to the overall plant metabolic landscape remains largely unexplored. Due to their early presence in the seed, seed-borne endophytic bacteria (SEB) can intimately colonize the plant´s endosphere while conferring a series of phytobeneficial services to their host. Understanding SEB dynamics is a crucial step for the formulation of microbial inoculants to improve plant fitness through the modulation of SEB functionality. In this work, non-inoculated and Herbaspirillum seropedicae-inoculated wheat (Triticum aestivum) roots were analyzed in order to explore the impact of inoculant-SEB-wheat interrelationships on the regulation of tryptophan (Trp) metabolism in the endosphere environment. Root inoculation with Hs led to phylum-specific changes in the SEB community composition at the genus level. This modulation shifted the metabolic potential of SEB communities in light of their capacity to modulate the levels of key Trp-related metabolites involved in both indole-3-acetic acid (IAA) biosynthesis and in the kynurenine (Kyn) pathway. Our results support a mode of action of Hs relying on a shift in SEB functionality which likely contributes to the regulation of root growth. We finally provide a conceptual framework illustrating that interactions among inoculants and SEB are critical to fine-tune the levels of IAA in the endosphere. Understanding the outcomes of these interactions is a crucial step towards the formulation of microbial inoculants based on their joint action with SEB communities to promote crop growth and health in a sustainable manner.